2020
DOI: 10.2196/17435
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Smartphone-Based Lifestyle Coaching App on Community-Dwelling Population With Moderate Metabolic Abnormalities: Randomized Controlled Trial

Abstract: Background Metabolic disorders are established precursors to cardiovascular diseases, yet they can be readily prevented with sustained lifestyle modifications. Objective We assessed the effectiveness of a smartphone-based weight management app on metabolic parameters in adults at high-risk, yet without physician diagnosis nor pharmacological treatment for metabolic syndrome, in a community setting. Methods I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 28 publications
(43 reference statements)
0
39
0
1
Order By: Relevance
“…Two systematic reviews have highlighted that a successful structured e-health program should be specifically tailored to the target group and have features that support self-monitoring, feedback, the use of theory, interactivity, and goal setting to change behavior. 16 , 38 , 39 Given that the same information on MetS was provided to the booklet group and to the app group, the members’ area and interactive platform and other features of the MetS app may have further facilitated the self-monitoring of individual health and the recording of exercise, body weight, and waist circumference, thereby enhancing the participants’ self-efficacy for adequate dietary control, exercise initiation, self-monitoring, and maintenance, leading to a greater amount of exercise and body weight reduction. 29–31 In addition, the alert and reminder functions of the app encouraged the participants to maintain their exercise habits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two systematic reviews have highlighted that a successful structured e-health program should be specifically tailored to the target group and have features that support self-monitoring, feedback, the use of theory, interactivity, and goal setting to change behavior. 16 , 38 , 39 Given that the same information on MetS was provided to the booklet group and to the app group, the members’ area and interactive platform and other features of the MetS app may have further facilitated the self-monitoring of individual health and the recording of exercise, body weight, and waist circumference, thereby enhancing the participants’ self-efficacy for adequate dietary control, exercise initiation, self-monitoring, and maintenance, leading to a greater amount of exercise and body weight reduction. 29–31 In addition, the alert and reminder functions of the app encouraged the participants to maintain their exercise habits.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have consistently shown a positive effect of increased physical activity on body weight control and lipid profile over a period of 3 or more months. 13 , 22 , 23 , 39 , 40 The success of other programs 13 , 16 , 22 , 23 , 40 may be due to their labor-intensive components, such as individual counselling for dietary and exercise advice or a supervised exercise program. However, our study relied solely on the app support, leading to an increase in the amount of physical exercise and weight reduction over the 3-month study period.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study retrospectively explores outcomes for better external validity, so that aspects of a formal clinical setting such as specific study timepoints or requirements do not inflate outcomes that individuals ordinarily manage on their own (18,19). The study used a global, highly assessed mHealth intervention called Noom that has been found to result in clinically significant weight loss in healthy and at-risk populations in observational studies and randomized controlled trials (RCTs) (20)(21)(22)(23)(24). RCTs have found that Noom reduced weight and body fat in individuals at risk for metabolic disorders, individuals with pre-diabetes, and individuals with colorectal polyps compared to control conditions (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Technology-mediated interventions can address these limitations and inconveniences while delivering reliable educational materials to many people at a convenient time and place [ 67 ]. People can receive consistently and the same intervention regardless of healthcare providers’ level of expertise.…”
Section: Discussionmentioning
confidence: 99%